Research on Training Model of English Talents under the Background of New Liberal Arts: – A Case Study of Liaoning Communication University - Li, Jiaqi (Transactions on Social Science, Education and Humanities Research, 2024)
Under the background of the construction of the new liberal arts, local application-oriented universities should explore the inter-disciplinarity of foreign language courses and application-oriented professional courses in combination with school-based characteristics and talent training objectives, and establish interdisciplinary curriculum groups. The model proposed in this paper combines the instrumental goal of improving students’ language foundation and cross-cultural ability with the humanistic goal of cultivating students’ independent learning ability, critical thinking ability and cultural accomplishment, so as to enable regional economic and social development.